Impact of pre-existing voids on electromigration in copper interconnects - Mario, Hendro (2013)
Previous in-situ electromigration experiments on copper interconnect have shown voids drifting towards the cathode, instead of nucleating at the cathode end. These voids could have pre-existed in the line before stressing and drifted towards the cathode. Furthermore, fatal voids observed from failure analysis that are located away from the cathode also strongly suggest, through modelling and simulation, that the voids grew from pre-existing ones. This failure mechanism is different under typical accelerated test conditions from what is expected at service conditions, and thus needs to be well understood. However, a design modification on the interconnect may help to reduce the impact of pre-existing voids on electromigration lifetime.